Resilience and associative stigma among mental health professionals in a tertiary psychiatric hospital: a cross-sectional study in Singapore - Edimansyah Abdin; Siow Ann Chong; Mythily Subramaniam; Louisa Picco; Sherilyn Chang; Qi Yuan (BMJ Open)
Objectives The mental health profession exposes healthcare workers to unique stressors such as associative stigma (stigmatisation that is extended from the stigmatised patients to psychiatric professionals and is based on affiliation with an individual with mental illness). Enhancing resilience, or the ability to ‘bounce back’ from adversity, is found to be useful in reducing occupational stress and its negative effects. In view of the high burnout rates reported among mental health professionals, this study aimed to examine resilience in this group of professionals and to explore the association between resilience and associative stigma.Design Observational study—cross-sectional design.Setting Tertiary psychiatry hospital in Singapore.Participants The study was conducted among 470 mental health professionals (doctors, nurses and allied health professionals) working in the hospital.Measures Resilience was assessed using the Brief Resilience Scale (BRS) and participants completed questionnaires that examined associative stigma. Participants provided their sociodemographic information, length of service, and information on whether they knew of a close friend or family member who had a mental illness.Results Mean resilience score for the overall sample was 3.59 (SD=0.64). Older age (β=0.012, 95% CI 0.004 to 0.019, p=0.003) and having known a family member or close friend with a mental illness (β=0.155, 95% CI 0.019 to 0.290, p=0.025) predicted higher BRS score. Associative stigma remained significantly associated with resilience score after controlling for sociodemographic factors whereby higher associative stigma predicted lower resilience scores.Conclusion The present finding suggests that resilience building programmes among mental health workers should target those of the younger age group, and that addressing the issue of associative stigma is essential.